2002
DOI: 10.1007/s00167-001-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of tunnel enlargement in anterior cruciate ligament reconstruction with hamstrings: extracortical versus anatomical fixation

Abstract: Changes in the femoral and tibial bone tunnel were studied prospectively after arthroscopic ACL reconstruction with quadruple hamstring autograft. To determine whether tunnel enlargement can be decreased by fixing the graft close to the joint line having a stiffer fixation construct we compared "anatomical" (one absorbable interference screw femorally, and bicortical fixation with two absorbable interference screws tibially) and extracortical fixation techniques (Endobutton femorally, and two no. 6 Ethibond su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
199
4
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(221 citation statements)
references
References 18 publications
11
199
4
7
Order By: Relevance
“…15 Buelow, Fauno, Iorio have all concluded that there was a significant reduction of tunnel widening using fixation points close to the joint compared to the system where the distance between fixation points is long. 11,14,28 In our study also, there was significantly less tunnel enlargement (p-value) with the use of interference screw as compared to suture disc. We have observed tunnel enlargement in the early postoperative period (2 weeks) probably because we have used extraction drilling.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…15 Buelow, Fauno, Iorio have all concluded that there was a significant reduction of tunnel widening using fixation points close to the joint compared to the system where the distance between fixation points is long. 11,14,28 In our study also, there was significantly less tunnel enlargement (p-value) with the use of interference screw as compared to suture disc. We have observed tunnel enlargement in the early postoperative period (2 weeks) probably because we have used extraction drilling.…”
Section: Discussionsupporting
confidence: 67%
“…[6][7][8][9] Tunnel enlargement is known to occur in first 6 months after ACL reconstruction and declines thereafter. 10,11 It is not seen 2 years after ACL reconstruction. No study has yet identified any effect on clinical stability or arthrometer measurements due to tunnel enlargement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buelow et al performed a prospective nonrandomized trial comparing femoral fixation with a bioabsorbable interference screw with an EndoButton. 14 The results demonstrated ACL reconstruction with a doubled semitendinosus and gracilis tendon graft and associated femoral and tibial tunnel enlargement. The authors found considerably more tunnel widening in the grafts fixed with extracortical fixation.…”
Section: Discussionmentioning
confidence: 96%
“…Sur les DIDT, aucune fixation osseuse ne fait l'unanimité. Dès les premiers jours, et ce quel que soit le mode de fixation utilisé, une ostéolyse des tunnels fémoraux et tibiaux s'opère (Buelow, Siebold, & Ellermann, 2002). Il y aurait unélargissement des tunnels qui se stabiliseraità six mois, ce qui nous inciteà rester prudents dans la sollicitation de la plastie.…”
Section: Renforcement Du Quadricepsunclassified